The relationship of anthropometrical characteristics and front crawl performance in male age-group swimmers - Marinho, D.A. (2011)
Swimming performance is affected by several factors including the swimming technique, the swimmer’s functional and metabolic characteristics and the level of training accomplishment. However, performance is also depending on the swimmer’s anthropometrical characteristics. The body shape, body size and body composition can play an important role to achieve higher performances.